Equine Articular Chondrocytes on MACT Scaffolds for Cartilage Defect Treatment. (16th January 2013) - Nürnberger, S.; Meyer, C.; Ponomarev, I.; Barnewitz, D.; Resinger, C.; Klepal, W.; Albrecht, C.; Marlovits, S.
Summary: Treatment of cartilage defects poses challenging problems in human and veterinary medicine, especially in horses. This study examines the suitability of applying scaffold materials similar to those used for human cartilage regeneration on equine chondrocytes. Chondrocytes gained from biopsies of the talocrural joint of three horses were propagated in 2D culture and grown on two different scaffold materials, hyaluronan (HYAFF ® ) and collagen (BioGide ® ), and evaluated by light and electron microscopy. The equine chondrocytes developed well in both types of materials. They were vital and physiologically highly active. On the surface of the scaffolds, they formed cell multilayers. Inside the hyaluronan web, the chondrocytes were regularly distributed and spanned the large scaffold fibre distances by producing their own matrix sheath. Half‐circle‐like depressions occasionally found in the cell membrane were probably related to movement on the flexible matrix sheath. Inside the dense collagen scaffold, only single cells were found. They passed through the scaffold strands by cell shape adaptation. This study showed that the examined scaffold materials can be used for equine chondrocyte cultivation. Chondrocytes tend to form multilayers on the surface of both, very dense and very porous scaffolds, and have strategies to span between and move in large gaps.